Fatores de risco associados à infecção hospitalar em uma Unidade de Terapia Intensiva - Figueiredo, Danielle Alves (2012)
Nosocomial infection is an important public health problem in recent years has contributed to increased rates of morbidity, hospital stay and greater costs. The range of invasive procedures performed in intensive care patients predisposes them to development of Nosocomial Infections. The objective of this study was analyze the incidence of nosocomial infections and the association with risk factors in the Intensive Care Unit. This is an observational study, non-concurrent cohort study, performed in the Intensive Care Unit of a Municipal Public Hospital in João Pessoa, on the period from January to October 2011. We included critically ill patients hospitalized for more than 24 hours in the Intensive Care Unit, a total sample of 244 patients. By the use of active search forms, The Hospital Department for Infection Control registration forms and Hospital Medical Records were identified cases of nosocomial infection and its main risk factors. In the data statistical analysis, showed that a total of 244 patients was observed: 51.6% (126/244) were male and 48.4% (118/244) females with a mean age of 63.02 years. The nosocomial infection rate was 23.4% (57/244). The most prevalent site was bloodstream/catheter-associated infection 38.59%, ventilation associated pneumonia 38.59% and urinary tract infection 21.05%. The main microorganisms involved in these infections were Pseudomonas aeruginosa (31.58%), Acinetobacter baumannii (15.79%) and Klebsiella pneumoniae (10.53%). The central venous access, mechanical ventilation, tracheostomy, nasogastric tube and length of Intensive Care Unit stay were considered risk factors for the occurrence of hospital infection. It is concluded that the high technology used in the Intensive Care Unit has prolonged patient survival. In contrast, there is an increased risk of cross infection in critically ill patients. Thus, urge the need for planning and implementing a process of specific protocols and measures well established, with multidisciplinary decisionmaking, with investments in continuing education to prevent and control infection thus contributing to the mitigation of risk factors and consequently reducing the rate of nosocomial infection.